A transcriptome analysis identifies molecular effectors of unconjugated bilirubin in human neuroblastoma SH-SY5Y cells - Calligaris, Raffaella (BioMed Central, 2009)
BACKGROUND: The deposition of unconjugated bilirubin (UCB) in selected regions of the brain results in irreversible neuronal damage, or Bilirubin Encephalopathy (BE). Although UCB impairs a large number of cellular functions in other tissues, the basic mechanisms of neurotoxicity have not yet been fully clarified. While cells can accumulate UCB by passive diffusion, cell protection may involve multiple mechanisms including the extrusion of the pigment as well as pro-survival homeostatic responses that are still unknown. RESULTS: Transcriptome changes induced by UCB exposure in SH-SY5Y neuroblastoma cell line were examined by high density oligonucleotide microarrays. Two-hundred and thirty genes were induced after 24 hours. A Gene Ontology (GO) analysis showed that at least 50 genes were directly involved in the endoplasmic reticulum (ER) stress response. Validation of selected ER stress genes is shown by quantitative RT-PCR. Analysis of XBP1 splicing and DDIT3/CHOP subcellular localization is presented. CONCLUSION: These results show for the first time that UCB exposure induces ER stress response as major intracellular homeostasis in surviving neuroblastoma cells in vitro.